(untitled) (Colombia Medica, 2012)
Introduction: Afebrile pneumonia syndrome in infants, also called infant pneumonitis, pneumonia caused by atypical pathogens or whooping cough syndrome is a major cause of severe lower respiratory infection in young infants, both in developing countries and in developed countries. Objective: To describe afebrile pneumonia syndrome in children . Methods: Through a cross-sectional study, we reviewed the medical records of children diagnosed with afebrile pneumonia treated at Hospital Universitario del Valle, a reference center in southwestern Colombia, between June 2001 and December 2007. We obtained data on maternal age and origin, prenatal care, the child’s birth, breastfeeding, vaccination status, symptoms, signs, diagnosis, treatment, and complications. Results: We evaluated 101 children with this entity, noting a stationary presentation: June-August and November- December. A total of 73% of the children were under 4 months of age; the most common symptoms were: cyanotic and spasmodic cough (100%), respiratory distress (70%), and unquantified fever (68%). The most common findings: rales (crackles) (50%), wheezing and expiratory stridor (37%); 66% were classified as mild and of the remaining 33%, half of them required attention in the intensive care unit. In all, there was clinical diagnosis of afebrile pneumonia syndrome in infants, but no etiologic diagnosis was made and despite this, 94% of the children received macrolides. Conclusions: These data support the hypothesis that most of these patients acquired the disease by airway, possibly caused by viral infection and did not require the indiscriminate use of macrolides.